Artificial Intelligence for Interpreting Medical Tests - Marina-Claudia-Cătălina MIRON (Applied Medical Informatics, 2023)
With the rapid development of technology, artificial intelligence (AI) has evolved over the past few years and has become increasingly present in the medical field. Recently, AI technology has been used for appointment scheduling, patient monitoring, and medical chatbots. We intend to develop software that will help people and doctors understand medical test results, such as blood tests and biopsies, more quickly and easily. By using optical character recognition (OCR) and a specially trained neural network, the software will be able to extract data from a document or image of the medical test results and predict a possible diagnosis. Our goal is to create an AI interpreter that uses easy-to-understand language. The interpreting software is intended to work as a telemedicine tool by connecting the patient and the doctor. We aim to create a digital method by which patients can upload results and communicate with their family doctor or specialists without the need to travel to the doctor’s office. We will assure the patient’s confidentiality by not sending their personal data along with the interpretation; instead, the doctor will receive only the patient’s ID. In conclusion, the AI software we will develop will make medical test result interpretation simpler and more accessible for people without a family doctor in their area.